Cavity backed slot antenna with SIW: article - Ruslan, Mohamad Naif; Subahir, Suhaila (UiTM, 2014)
A low profile planar cavity backed slot antenna (CBSA) with substrate integrated waveguides (SIW) operating at 4.78ghz for wireless applications has been described in this paper. This antenna is completely designed at a single substrate which is a fr-4 with dielectric constant, εr = 4.4 and 1.6mm thickness. The design consists of a SIW antenna with patch, feeding and cavity backed. Grounded co-planar waveguide (GCPW) is used as feeding element to stimulate the SIW cavity to replace microstrip line feeding. The proposed antenna have been designed, simulated and measured using CST microwave studio software and vector network analyze (VNA) respectively. Antenna parameters result such as return loss (s11), radiation pattern, directivity, gain and VSWR are investigated, compared and analysed. The tuning length of slot and GCPW length have also been analyzed.